Traffic pollution modelling in a complex urban street - Venegas, Laura Esperanza (2012)
This study explores for the first time, the applicability of the Danish Operational Street Pollution Model (OSPM) in the city of Buenos Aires where street canyons are very irregular. The model is applied in an irregular and asymmetric street canyon of a five-lane avenue near a street intersection. Urban background concentrations estimated by the DAUMOD model are considered. Meteorological information registered at the domestic airport located in the city is used in calculations. Three months of hourly NOx, NO 2 and CO estimated concentrations are compared with measurements inside the street canyon. Statistical evaluation of model results shows that OSPM performance is quite good.